(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In emergency situations, danger can arise due to 2 different reasons. These are natural and man-made causes. In this article, we will cover the prevention of accidents in emergency situations caused not only by natural but also man-made hazards. In the Republic of Uzbekistan, state cadastres of zones with high natural and man-made hazards are maintained by the Ministry of Emergency Situations. Due to this, the prevention of victims and accidents in emergency situations is organized more effectively. Due to 3D mapping in Uzbekistan, we will highlight the priority factors in maintaining cadastres of natural and man-made danger zones. It will also be explained which organizations in Uzbekistan maintain this type of cadastres and collect data.